LIST OF LAND SNAILS IN JAVA AND SEVERAL ADJACENT ISLANDS - Ayu Savitri Nurinsiyah (TREUBIA, 2021)
The malacofauna of Java has been most studied among the Indonesian islands, but the list of land snails in the area remains outdated. This study presents an updated check list of land snails in Java and its adjacent islands. This list is a compilation data from field work in Java conducted in 2013-2016, records from various museums in Europe and Indonesia, collections from private collectors, data from citizen sciences, and literatures. In total, 263 land snail species were recorded in Java and its adjacent islands. The number comprises of 36 families i.e. Subclass Neritimorpha (2 families), Caenogastropoda (6 families), and Heterobranchia (28 families). About 40% are species endemic to Java and among them have restricted distribution to certain areas. In addition, 5% or 13 introduced species were recorded in Java.